Radioactive isotope analysis of sediment core PS115/2_2 - Stein, Ruediger; Frederichs, Thomas; Fahl, Kirsten; Geibert, Walter; Matthiessen, Jens; Niessen, Frank; Vogt, Christoph; Sassenroth, Cynthia; Bazhenova, Evgenia A (In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Our age model, a fundamental prerequisite for any kind of paleoclimatic reconstruction, is based on magnetostratigraphy, 230Th and 231Pa excess (230Thex and 231Paex) records, and AMS14C ages. The radioisotopes 230Th, 232Th, 231Pa, 234U and 235U (238U) were analysed by means of isotope dilution sector field ICP-mass spectrometry (SF-ICP-MS). As independent age control proxies, extinction ages of 230Thex and 231Paex have been determined (cf., Hillaire-Marcell et al., 2017; Geibert et al., 2021; Song et al., 2023). For details and methods, we refer to Stein et al. (this paper).
Keywords: Arctic Ocean; Eurasian Ice Sheet History; Late Pleistocene; Organic carbon (OC) burial